Refleksi Misi Gereja melalui Pembacaan Narasi Kota Babel - Deni Citra Damai Telaumbanua (Sekolah Tinggi Teologi Baptis, Jakarta, 2023)
The church has not escaped the Covid-19 pandemic, but the church must not ignore God's mission for her because of the Covid-19 pandemic. In this paper, the author describes the story of the city of Babel from Genesis 11:1-9, where humans disobeyed God's mission to carry out cultural mandates as the reason for its creation. God must intervene as a punishment for them while simultaneously declaring His grace by returning humans to His original mission: to spread them all over the earth. Using the Proflective Church of Joas Adiprasetya, the author reflects on the story of the city of Babel on the post-Covid-19 church mission. The church, which is